A Body Mass Index Measuring Tool with Ultrasonic Sensor and Load Cell (OBEMETER) - rahman, Syaifur; Suryadi, Dedy; Aula, Abqori (ELKHA : Jurnal Teknik Elektro, 2025)
Body Mass Index (BMI) is a parameter often used to evaluate the health status based on someone"™s height and weight ratio. However, the current existing BMI measurement and calculation are done manually. This research aims to develop an automatic BMI measuring tool called Obesity Meter (OBEmeter), by displaying the BMI score and body weight status. OBEMeter utilizes two sensors, namely ultrasonic (HC-SR04) to measure body height and load cell (HX711) to measure body weight. The use of ultrasonic sensors (HCSR04) and load cells (HX711) provides consistent height and weight measurements under various user conditions compared to other types of sensors. The height and weight data are then processed by Arduino in which the BMI calculation algorithm is already embedded. The BMI value is then converted into five-level body weight statuses, i.e. "ceking (underweight), kurus (slim), normal, kelebihan (overweight), and obese". This instrument is equipped with buzzer as an indicator if the BMI value is within the obese category. Our approach improves the measurement and calculation process by performing body and height measurement, then displaying the BMI in very short time automatically. Experimental results show that the reading accuracy of the ultrasonic sensor and load cell sensor are above 95%. Then, test results on 15 users show that the OBEmeter can produce the BMI measurement with 95,79% accuracy, which indicates that it can be utilized as a self-assist device to monitor the user"™s health status practically.